Corruption, shadow economy and income inequality: Evidence from Asia - Saibal Kar; Shrabani Saha (Institute for the Study of Labor (IZA), 2012)
A number of recent studies for Latin America show that as the size of the informal economy grows, corruption is less harmful to inequality. We investigate if this relationship is equally compelling for developing countries in Asia where corruption, inequality and shadow economies are considerably large. We use Panel Least Square and Fixed Effects Models for Asia to find that both Corruption Perception Index and ICRG index are sensitive to a number of important macroeconomic variables. We find that in the absence of the shadow economy, corruption increases inequality. However, with larger shadow economies in South Asia, the income inequality tends to fall.
Keywords: J48; K42; O17; O53; 330; corruption; inequality; shadow economy; panel data; South Asia; Korruption; Schattenwirtschaft; Einkommensverteilung; Schätzung; Asien